Blockade of endoplasmic reticulum stress‐induced cell death by Ureaplasma parvum vacuolating factor. (11th October 2021) - Nishiumi, Fumiko; Kawai, Yasuhiro; Nakura, Yukiko; Yoshimura, Michinobu; Wu, Heng Ning; Hamaguchi, Mitsuhide; Kakizawa, Shigeyuki; Suzuki, Yo; Glass, John I.; Yanagihara, Itaru
Abstract: Previously, we found that Ureaplasma parvum internalised into HeLa cells and cytosolic accumulation of galectin‐3. U. parvum induced the host cellular membrane damage and survived there. Here, we conducted vesicular trafficking inhibitory screening in yeast to identify U. parvum vacuolating factor (UpVF). U. parvum triggered endoplasmic reticulum (ER) stress and upregulated the unfolded protein response‐related factors, including BiP, P‐eIF2 and IRE1 in the host cells, but it blocked the induction of the downstream apoptotic factors. MicroRNA library screening of U. parvum ‐infected cells and UpVF‐transfected cells identified miR‐211 and miR‐214 as the negative regulators of the apoptotic cascade under ER stress. Transient expression of UpVF induced HeLa cell death with intracellular vacuolization; however, some stable UpVF transformant survived. U. parvum ‐infected cervical cell lines showed resistance to actinomycin D, and UpVF stable transformant cell lines exhibited resistance to X‐ray irradiation, as well as cisplatin and paclitaxel. UpVF expressing cervical cancer xenografts in nude mice also acquired resistance to cisplatin and paclitaxel. A mycoplasma expression vector based on Mycoplasma mycoides, Syn‐MBA (multiple banded antigen)‐UpVF, reduced HeLa cell survival compared with that of Syn‐MBA after 72 hr of infection. These findings together suggest novel mechanisms for Ureaplasma infection and the possible implications for cervical cancer malignancy. Take Aways: Ureaplasmal novel virulence factor, UpVF, was identified. UpVF triggered ER stress but suppressed apoptotic cascade via miR‐211 and ‐214. UpVF conferred resistance to anticancer treatments both in vivo and in vitro. Dual expression of MBA and UpVF in JCVI‐syn3B showed host cell damage. Abstract : A novel virulence factor, Ureaplasma parvum vacuolating factor (UpVF), was identified. UpVF induced cell vacuolation and triggered ER stress in host cells. In contrast, UpVF blocked the downstream apoptotic cascade through the upregulation of host cellular miR‐211 and miR‐214. UpVF expressing tumour cell lines showed resistance to anticancer drugs and X‐ray irradiation. Xenograft of UpVF expressing tumour cells reduced the efficacy of anticancer agents in nude mice.